472. ROUTINE PLACEMENT OF FEEDING TUBES SHOULD BE AVOIDED IN ESOPHAGEAL CANCER PATIENTS UNDERGOING SURGERY. (24th September 2022) - Shi, Ge; Malthaner, Richard; Nayak, Rahul; Fortin, Dalilah; Inculet, Richard; Qiabi, Mehdi
Abstract: Perioperative nutritional optimization of patients undergoing esophagectomy for cancer is important as this population is prone to malnutrition associated with poor outcomes. Nutritional supplementation has been achieved via enteral nutrition through percutaneous feeding tubes such as gastrostomy tubes (G-tubes) and jejunostomy tubes (J-tubes). These are not benign and are associated with adverse events including infections, dislodgement, increased healthcare visits, among others. We aim to determine factors associated with adverse outcomes after feeding tube placement. Patients who underwent esophagectomy for carcinoma and had at least one feeding tube placed from November, 2017 to October, 2021 at a single institution were retrospectively reviewed. Subgroup analyses were performed testing for revelant chracteristics. Wilcoxon rank sum test was used to analyze non-parametric continuous data, and Chi-Square and Fisher's exact test for categorical variables. Univeriate and multivariate logistical regression analyses were conducted evaluating outcomes of interests. The primary outcome was the overall rate of tube-related complications. 136 patients were included with 201 feeding tubes placed. The rate of adverse events related to feeding tubes was 39%. Of these, 11% were wound infections, 16% required procedural intervention, 11% visited the Emergency Department due to feeding tube-related complications. Smoking history was a significant risk factor for complications compared to never-smokers (44% vs. 24%, p=0.011). Females had increased complications compared to males (58% vs. 35%, p=0.010). Comorbid patients (Charlson Comorbidity Index 5-6) were more likely to suffer from tube-related complications (OR=4.47, p=0.038). There were no significant differences seen in complications rates comparing G- and J-tubes (32% vs. 43%, p=0.11). There is significant morbidity related to feeding tubes. The risk profile of these tubes should be carefully discussed. Routine use of feeding tubes in esophagectomy patients should be avoided.